1999
DOI: 10.1212/wnl.52.5.1038
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral lateralization of language in normal left-handed people studied by functional MRI

Abstract: Silent word generation lateralizes to the left cerebral hemisphere in both handedness groups, but right-hemisphere participation is frequent in normal left-handed subjects. Exclusive right-hemisphere activation rarely occurred in the frontal lobe region studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
348
3
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(408 citation statements)
references
References 31 publications
47
348
3
10
Order By: Relevance
“…There is also a weak correlation between handedness and the lateralized representation of language in the human brain. Studies based on the Wada test (Rasmussen & Milner 1977), electroconvulsive therapy (Warrington & Pratt 1973) and brain imaging (Pujol et al 1999;Knecht et al 2000) are reasonably consistent in showing that over 90 per cent of right-handers are left-cerebrally dominant for language, compared with approximately 70 per cent of left-handers. These estimates can be matched by McManus's model with p(D)Z0.8, on the assumption that handedness and cerebral dominance for language are subject to the same biases in the three genotypes, but that the biases are applied independently (table 2).…”
Section: Genetic Theoriesmentioning
confidence: 92%
“…There is also a weak correlation between handedness and the lateralized representation of language in the human brain. Studies based on the Wada test (Rasmussen & Milner 1977), electroconvulsive therapy (Warrington & Pratt 1973) and brain imaging (Pujol et al 1999;Knecht et al 2000) are reasonably consistent in showing that over 90 per cent of right-handers are left-cerebrally dominant for language, compared with approximately 70 per cent of left-handers. These estimates can be matched by McManus's model with p(D)Z0.8, on the assumption that handedness and cerebral dominance for language are subject to the same biases in the three genotypes, but that the biases are applied independently (table 2).…”
Section: Genetic Theoriesmentioning
confidence: 92%
“…The hand preference should be taken into account (Pujol et al 1999;Knecht et al 2000) when studying the language plasticity as linear relationship has been shown between handedness and atypical dominance, with increased incidence of the reorganisation in strong left-handed patients. In the present study, at a fi rst glance, our results did not show correlation between handedness and MR signal intensity values measured in left and right ROIs.…”
Section: Associated Hippocampal Sclerosismentioning
confidence: 99%
“…Verbal information is processed more efficiently when presented to the right than the left ear (Belin et al, 1998;Kimura, 1961) due to the hemispheric asymmetry in language processing, with Broca's speech area located in the left hemisphere, (Belin et al, 1998;Pujol, Deus, Losilla, & Capdevila, 1999;Toga & Thompson, 2003). The literature suggests that there should be an overall shift towards a right channel bias for loudness judgments for all time-related words.…”
Section: Study 32mentioning
confidence: 99%